The impact of Basel III on the provision on long-term housing finance in South Africa - MacKenzie, Peter Graham (Department of Construction Economics and Management, 2019)
South Africa suffers from an acute housing shortage with the lack of access to credit partly to blame. The implementation of Basel III, an international regulatory framework touted to impact the banking sector, has been suggested as a potential catalyst to credit deterioration in South Africa. The purpose of this study is to assess the impact of the Basel III regulatory Accord on the provision of long - term housing finance in South Africa. A combination of interviews with bank personnel, as well as a time – series statistical analysis utilising aggregate bank balance sheet data is employed to gauge how changes in banks’ balance sheet compositions may affect long - term housing finance. South African banks are historically well capitalised. However, the introduction of newly developed parameters in accordance with the Basel III Accord appear to threaten bank profitability. Findings from the study indicate that the provision of long - term housing finance will be compromised in certain ways with some sectors of the housing market more impacted than others.